A technical review on coke rate and quality in low-carbon blast furnace ironmaking. (15th March 2023) - Rahmatmand, Behnaz; Tahmasebi, Arash; Lomas, Hannah; Honeyands, Tom; Koshy, Pramod; Hockings, Kim; Jayasekara, Apsara
Highlights: Measures for reducing the carbon intensity of blast furnace ironmaking were introduced. Influences of low-carbon ironmaking processes on fuel requirements are reviewed. The introduction of alternative reductants cannot eliminate the need for metallurgical coke. Sustainability of blast furnace ironmaking depends on improving the H/C replacement ratio. Introduction of hydrogen promotes the solution loss and structural degradation of coke. Abstract: The blast furnace technology is still the main ironmaking route with a current global share of 70%. Reduction of fossil carbon consumption and CO2 emissions in blast furnace operations are essential for the decarbonization of steelmaking. Potential solutions such as introducing renewable carbon-based materials (torrefied biomass, charcoal), using hydrogen-enriched reducing gases (i.e., hydrogen gas, coke oven gas, reformed coke oven gas, green methane), oxygen enrichment with top gas recycling, and carbon capture and storage/utilization have been considered to decrease emissions. The enhanced sustainability of blast furnace operations depends primarily on improving the hydrogen-to-carbon replacement ratio. Hydrogen is an effective reducing agent, producing steam during the reduction of ferrous burden. The replacement of coke and PCI with hydrogen leads to reduced fuel rates and CO2 emissions. Although implementing the innovative ironmaking solutions reduces coke and coal consumption, coke cannot be replaced entirely as it plays an irreplaceable role as a mechanical support network and the permeable layer for gas movement in the blast furnace. The injection of alternative reducing agents into the blast furnace alters the reaction environment by changing gas composition and temperature. Therefore, understanding the impacts of new reaction conditions on coke rate and quality requirements is important to both coal producers and steel manufacturers. This paper reviews the current understanding of how the introduction of alternative reducing agents into the blast furnace influences the gasification behavior, degradation mechanism, and consumption rate of coke. The review also identifies the knowledge gaps and future research opportunities in the field.